2008
DOI: 10.1097/jcp.0b013e31818a6cfd
|View full text |Cite
|
Sign up to set email alerts
|

A 2-Year Prospective Follow-Up Study of Lower Urinary Tract Symptoms in Patients Treated With Clozapine

Abstract: Urinary incontinence and enuresis are well-known side effects of clozapine. However, clinical experience has shown that patients also suffer from diverse lower urinary tract symptoms (LUTS). The natural course of clozapine-related LUTS is unclear. Thus, a longitudinal follow-up study is needed. A total of 101 subjects who were taking clozapine initially participated. Their LUTS were evaluated using the International Prostate Symptom Score (IPSS), other questionnaires, and a medical records review. After 2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…-Two studies assessed the CANE point prevalence (nocturnal enuresis at the time of assessment) using a cross sectional approach (Centorrino et al 1994, Long et al 2015). -Two studies provided a 1 month prevalence using a retrospective approach (Jeong et al 2008, Yusufi et al 2007 o A Jeong et al 2008 assessment was part of a 2-year prospective follow-up study. -Four studies assessed the CANE episode prevalence (nocturnal enuresis since beginning of clozapine) using a retrospective approach (Bhirud, Shah.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…-Two studies assessed the CANE point prevalence (nocturnal enuresis at the time of assessment) using a cross sectional approach (Centorrino et al 1994, Long et al 2015). -Two studies provided a 1 month prevalence using a retrospective approach (Jeong et al 2008, Yusufi et al 2007 o A Jeong et al 2008 assessment was part of a 2-year prospective follow-up study. -Four studies assessed the CANE episode prevalence (nocturnal enuresis since beginning of clozapine) using a retrospective approach (Bhirud, Shah.…”
Section: Resultsmentioning
confidence: 99%
“…Mean age ranged from 37 to 41.5 years. Jeong et al (2008) observed a higher frequency of nocturnal enuresis in women compared to men. This study was comprised of 60% males.…”
Section: Clozapine Dosage and Concurrent Medicationsmentioning
confidence: 90%
“…In a previous clinical study of LUTS measured using an adapted version of the IPSS scale among 101 clozapine users, women had only non-significantly higher mean scores compared to men (7.78 and 7.18, respectively). [12] Because AAPs are not currently indicated as first-line therapy for depression, it is reasonable to speculate that women using AAPs alone had more severe, potentially uncontrolled depression even after adjustment for residual depressive symptoms. However, we observed similar associations comparing joint users of SSRIs and AAPs to AAP-only users, suggesting that 'confounding by severity' did not explain the association.…”
Section: Discussionmentioning
confidence: 99%
“…We defined the presence of LUTS as a score of ≥8, corresponding to moderateto-severe symptoms. For graphical displays, LUTS severity categories were defined using the AUA-SI as follows: no symptoms (score=0), mild (1-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), severe (≥20). We also examined mean storage and voiding storage subscales of the AUA-SI.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation